Regional redistribution through SBA guaranteed loan programs - Lee, Churn Ken; Lee, Munseob (Journal of Corporate Finance, 2023)
We document and quantify a new implicit transfer mechanism in the SBA 7(a) loan program that redistributes funds between US states. We use SBA 7(a) loan data in conjunction with Dealscan private corporate loan data to show that SBA 7(a) loan interest rates are much less responsive to predicted local loan default risk compared to private corporate loans. This redistributes funds from states with low default risk to states with high default risk. These transfers are positively correlated with the severity of local economic shocks during the Great Recession and the COVID-19 Recession. Therefore, even though it was unintended, the interest rates on SBA 7(a) loans acted as an automatic stabilizer mitigating regional economic shocks.